Rok 1968 – koniec i początek - Friszke, Andrzej (Studia Polityczne, 2018)
The year 1968 marked the end of development processes in the formation of ideological and legitimating formulas in the Polish United Workers’ Party (PZPR) and its subordinate institutions, as well as among circles counting on significant changes. Initiated in 1956, these formulas assumed the search for the legitimacy of the regime by combining the ideological content of the post-Stalinist version of communism with the democratisation and ‘nationalisation’ of the political system. The rejection of the democratisation process and the restoration of the monopoly of central government by Gomułka’s regime pushed it to seek nationalist affirmation. March 1968 brought a rebellion by students demanding democratisation, recognition of and respect for civil rights from the authorities. The authorities responded with repression, which was particularly intense between 1956 and 1981. There were numerous arrests and extensive purges in administration institutions, at universities and in cultural institutions. The purges were accompanied by anti-Semitic slogans, and the document published here proves that the racial criterion was imposed by a special order by the minister of internal affairs. The analysis shows that the purges took place under conditions of significant independence of middle-level party activists allied with the ministry’s leaders, which undermined the hierarchy of subordination to the highest positions of PZPR. The year 1968 closed the period of post-October hopes and illusions, marked the departure of the generation of pre-war communists from positions, and the reference to anti-Semitism meant the rejection of fundamental and universal leftist values. Although the anti-Semitic campaign slowed down, the criterion of Jewish origin remained important in assessing citizens and determining prospects for promotion for many years to come. The breakdown of ideology created a path to the only pragmatic justification of the regime’s legitimacy. The opponents of the regime, who referred to the 1956 hopes, gave up hope that the system would ever evolve towards democracy (in general terms, the invasion of Czechoslovakia was no less important than Polish events). This opened the way to seeking opposition activities outside the existing system. This path was followed by the participants of the March 1968 movement, which became a formative experience for thousands of young intellectuals. Then they became active participants of the democratic opposition and Solidarity movement.